The Contextualization of Sharia and Its Contribution to The Development Of The Indonesian National Law - Mahmudah, Siti (Universitas Islam Negeri Raden Intan Lampung, 2019)
This article asserts an argument that sharia needs to be contextualized along with changing conditions, place and time. The reason is very clear, Islam and the initial Islamic Shari’a revealed in Mecca in 610 AD were very flexible and contextual. Islam accepts Hanif religion (the religion of Prophet Ibrahim) with the aim of perfecting the Hanif religion which has been misunderstood, perpetuating the teachings of the good and great Hanif religion, and rectifying its teachings to perpetuate its noble and invaluable teachings. Islam also respected Arab tradition as well to perpetuate noble and beneficial Arab traditions, and to remove the traditions that were no longer beneficial. This is the foremost nature of Islam according to Khalil Abdul Karim which he termed as a blueprint for the practice of Islam and Islamic law in today’s public space. Religion is for humans, as Allah the Most Just is very concerned with the realities of the social life of people. The law is also created to discipline the community life, and therefore, its main concern is the benefit of human life,. In this context, the historicity of the initial Shari’a can be used as the basis in applying Islamic law anywhere and anytime.